AB0382 Outcomes of etanercept therapy in elderly rheumatoid arthritis patients: an investigation of the akita orthopedic group on rheumatoid arthritis registry. (15th June 2017) - Aonuma, H; Kashiwagura, T; Urayama, M; Kobayashi, M; Aizawa, T; Sugimura, Y; Miyakoshi, N; Shimada, Y
Abstract : Background: The Akita Orthopedic Group on Rheumatoid Arthritis (AORA) encompasses 32 physicians and 28 clinics providing medical care to rheumatoid arthritis (RA) patients in Akita Prefecture, Japan. The patient registry for this group (the AORA registry) reflects actual clinical data on RA therapy in Akita, where the proportion of elderly (age ≥65 years) residents in the population is the highest in Japan. Etanercept (ETN) is a tumor necrosis factor inhibitor reportedly associated with fewer adverse event-related treatment discontinuations than other drugs of this class. However, few evaluations of the efficacy and safety of ETN have been reported for elderly populations. Objectives: Based on data from the AORA registry, we aimed to investigate the continuation rate for ETN therapy, reasons for discontinuation, and therapeutic effects among elderly RA patients living in Akita. Methods: Among 204 AORA-registered patients starting ETN therapy between January 2009 and August 2014, data for the 73 patients (35.8%) who were ≥65 years old at the initiation of therapy were evaluated. Mean age was 72.4±4.7 years (range 65–83 years), and 79.5% were women. Mean disease duration was 15.1±12.6 years (range 9 months-55 years), 13.7% of patients were switching from another biologic agent, 49.3% could perform activities of daily living (ADL) independently, and 65.8% had at least one of the following comorbidities: hypertension, diabetes, respiratory disorder, cardiovascular disease, and cerebrovascular disease. We evaluated the 1-year cumulative continuation rate for ETN therapy using the Kaplan–Meier method, and investigated the characteristics of patients who discontinued treatment because of adverse events (AE cohort) or lack of efficacy (LOE cohort). We evaluated efficacy in 55 patients for whom Disease Activity Score – C-reactive protein assessments were possible, based on European League Against Rheumatism (EULAR) criteria. Results: The 1-year cumulative continuation rate for ETN therapy was 87.2%, and 24 patients discontinued treatment. The AE and LOE cohorts contained 12 and 7 patients, respectively. The AE cohort had a mean age of 75.5 years at the start of treatment, with a mean disease duration of 20.7 years, 8.3% of patients switching from another biologic agent, 16.7% performing ADL independently, and a comorbidity rate of 100%. Corresponding values for the LOE cohort were: mean age, 71.4 years; disease duration, 12.7 years; switching from another biologic agent, 42.9%; performing ADL independently, 57.1%; and comorbidity rate, 28.6%. Efficacy was noted for 81.8% of all patients with 52 weeks of ETN therapy, achieving good efficacy in 21 cases and moderate efficacy in 24 cases. Conclusions: Retention rate and efficacy were considered satisfactory in elderly RA patients receiving ETN therapy. The risk of adverse events was suggested to increase with increasing age, declining ADL, and presence of comorbidities. These factors require attention when prescribing ETN therapy. References: Cho SK, Sung YK, Kim D, et al. Drug retention and safety of TNF inhibitors in elderly patients with rheumatoid arthritis. BMC Musculoskelet Disord. 2016; 17: 333. Disclosure of Interest: None declared